Language Learning Strategies in Teaching Speaking: A Case Study at SMK Negeri Nibaaf - Ua, Pricila Ines; Luruk, Fransiska Densiana; Bouk, Edmundus (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2025)
This study investigated the language learning strategies, defined as the intentional techniques used by teachers to facilitate students’ language development, employed by English teachers in teaching speaking at SMK Negeri Nibaaf. The purpose of the research was to identify the strategies that the teachers used and the challenges that they faced. A descriptive qualitative method was employed, and two English teachers participated in the study. Data were collected through classroom observations and interviews. The non-participant classroom observation was employed in three meetings. To support the observation, the semi-structured interview was addressed to two English Teachers. The data was analyzed in three stages: data reduction, data display, and conclusion drawing. Data reduction involved selecting and focusing on relevant information, data display was conducted through descriptive narrative, and the final stage involved drawing conclusions to answer the research questions. The findings revealed that the teachers implemented several strategies, including showing and telling, setting clear lesson goals, providing flexible time, encouraging collaborative work, and giving feedback. These strategies were effective in enhancing students’ speaking performance, as most students became more confident and willing to speak English. However, some challenges persisted, such as limited vocabulary, shyness, and pronunciation difficulties. The study concluded that effective strategies significantly improved students’ speaking skills, but teachers needed to continuously adapt their approaches to address learning problems.